News Representation Of 212 Reunion on The Harian Republika, Jawa Pos, Rakyat Merdeka, and Kompas - Sabbardi, Muhammad; Mardikantoro, Hari Bakti; Joko Santoso, Wahyudi (Universitas Negeri Semarang, 2022)
The language in the mass media has different backgrounds and ideologies to lead public opinion in framing the news discourse. Language in this context has been formed by an ideology background that carries a certain charge of power in reporting the 212-movement action reunion. This lead researcher interested to examine the representation of the 212-reunion news in the Republika, Jawa Pos, Rakyat Merdeka, and Kompas. The purpose of this study is to describe the textual dimensions, interpret discursive practices, and explain the sociocultural dimensions of reporting on the Harian Republika, Jawa Pos, Rakyat Merdeka, and Kompas in the construction of 212 reunion representations. This research used descriptive qualitative and Faircloguh Discourse Analysis theoretical approach in identifying and analyzing the data. Based on data analysis, the following results were obtained. First, the 212-action reunion is represented positively and negatively. The procedure of this representation can be seen from the vocabulary, grammatical, and textual structures used by the Harian Republika, Jawa Pos, Rakyat Merdeka, and Kompas. Second, the positive and negative representations are determined by the discourse practices of the four-mass media, such as supporting, rejecting, or leading public opinion as desired by the mass media. Third, the socio-culture of media coverage of the 212-action reunion is influenced by media institutions, the media economy, political institutions, and sociocultural processes that develop in society.